The Urgency of Learning Arabic in Understanding the Meaning of the Qur'an (Analysis of Q.S Yusuf Verse 2) - Anah Patimah (Konsultan Jurnal Ilmiah Indonesia, 2024)
Arabic is the most important source in understanding the Qur'an. In the science of interpretation, the Arabic language has urgency, among other things, to know the semantic meaning of the verses of the Qur'an, and to know the meaning contained in the verses. Arabic is also used as a reference in understanding and interpreting the Qur'an. Speaking Arabic and the Qur'an is a unity that cannot be separated from one another. The Qur'an was revealed using the Quraish dialect of Arabic. The Quraish dialect that comes from the Quraish tribe that occupied the city of Makkah and has gained a leading place among the northern Arabic dialects, is the main contributor to the birth of the Fushha Arabic language through al-Naqsy language and Jahili literature. Caliph Uthman bin Affan established the Quraysh dialect as the only dialect used to write the Qur'an.